The Socio-Cultural Embeddedness of Individuals' Ethical Reasoning in Organizations (Cross-cultural Ethics) - Thorne, Linda (Journal of business ethics, 2002)
While models of business ethics increasingly recognize that ethical behavior varies cross-culturally, scant attention has been given to understanding how culture affects the ethical reasoning process that predicates individuals' ethical actions. To address this gap, this paper illustrates how culture may affect the various components of individuals' ethical reasoning by integrating findings from the cross-cultural management literature with cognitive-developmental perspective. Implications for future research and transnational organizations are discussed.